An Acceptance Analysis of Subsoil Amelioration Amongst Agricultural Actors in Two Regions in Germany - Hinzmann, Mandy; Ittner, Sophie; Kiresiewa, Zoritza; Gerdes, Holger (Frontiers in Agronomy, 2021)
The subsoil, commonly defined as horizons below the working depth of 30 cm, often receives little attention in farming practice. Yet plants extract between 10% and 80% of their nutrient and water requirements from the subsoil. Recent research indicates that subsoil amelioration measures, which enhance water storage capacity, root penetration and microbial activity, could contribute to stabilizing yields in times of drought. Therefore, we investigated farmers’ and other soil experts’ perceptions of subsoil amelioration as an approach to adapt to climate change as well as the factors that influence their willingness to adopt specific measures to improve the subsoil. We applied the Q-method combined with focus groups in two case study regions in Germany. Two subsoil amelioration techniques were considered: 1) Deep loosening combined with the incorporation of compost into deep soil layers (30-60 cm) and 2) the cultivation of alfalfa as deep-rooting pre-crop. Our results show three distinct views on subsoil amelioration, which we termed as the ‘pioneers’, the ‘skeptics’ and the ‘ecologists’. While the pioneers were open towards applying deep loosening combined with incorporation of compost into the subsoil, the skeptics had concerns about the method and perceived it as hardly feasible in practice, and the ecologists clearly preferred biological approaches such as alfalfa cultivation. Despite the different views, all three perspectives view subsoil amelioration as a useful approach to adapt to changing climate conditions. In conclusion, we identified a number of factors that influence the willingness to implement specific techniques to improve the subsoil: economic considerations, awareness of subsoil functions, environmental awareness, individual norms and beliefs as well as risk perception. We recommend to consider these factors in the design of a policy framework that promotes subsoil amelioration in Germany. Our findings could be of relevance for agricultural systems around the world which are prone to drought risk.